Inter-Municipal Governance Networks: Application of Exponential Random Graph Models in Los Lagos, Chile; [Redes de Governança Intermunicipal: Aplicação de Modelos de Gráficos Aleatórios Exponenciais Em Los Lagos, Chile]; [Redes de Gobernanza Intermunicipal: Aplicación de Modelos de Grafos Aleatorios Exponenciales en la Región de Los Lagos, Chile] - Arias-Yurisch, K (Fundacao Getulio Vargas, 2023)
The idea of governance has permeated the debates on the state’s transformation at the regional level since the 1990s. However, operationalization difficulties have limited our knowledge of the phenomenon. This article contributes to filling this gap by examining the inter-jurisdictional dimension of regional governance. From a network perspective, the article studies the emergence of inter-municipal networks from different local collaborative mechanisms. Based on the institutional collective action framework, the study analyzes the prevalence of network structures associated with different types of social capital (bonding/bridging) in three inter-municipal networks in the Los Lagos Region in Chile. The application of exponential random graph models (ERGM) revealed evidence supporting the consistent prevalence of bonding in the three networks studied. The findings also showed the networks’ coexistence with structures decentralized in more complex regional networks. © 2023, Fundacao Getulio Vargas. All rights reserved.